2015
DOI: 10.1093/gbe/evv145
|View full text |Cite
|
Sign up to set email alerts
|

The Genome of Winter Moth (Operophtera brumata) Provides a Genomic Perspective on Sexual Dimorphism and Phenology

Abstract: The winter moth (Operophtera brumata) belongs to one of the most species-rich families in Lepidoptera, the Geometridae (approximately 23,000 species). This family is of great economic importance as most species are herbivorous and capable of defoliating trees. Genome assembly of the winter moth allows the study of genes and gene families, such as the cytochrome P450 gene family, which is known to be vital in plant secondary metabolite detoxification and host-plant selection. It also enables exploration of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(76 citation statements)
references
References 100 publications
5
71
0
Order By: Relevance
“…The Tpit ‐SP assembly also had a GC content of 37% which is very close to the other Noctuoidea species, S. frugiperda (36% for both strains, Gouin et al., ). However, the proportion of repeated elements of 45% (Table ) was higher than those found for S. frugiperda (29% for both strains, Gouin et al., ) and closer to the values found for B. mori (44%) and O. brumata (54%; Derks et al., ; International Silkworm Genome Consortium, ). Furthermore, 605 duplicated regions (average length: 1,348 bp, range 809–8,509 bp) were identified in 540 scaffolds.…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…The Tpit ‐SP assembly also had a GC content of 37% which is very close to the other Noctuoidea species, S. frugiperda (36% for both strains, Gouin et al., ). However, the proportion of repeated elements of 45% (Table ) was higher than those found for S. frugiperda (29% for both strains, Gouin et al., ) and closer to the values found for B. mori (44%) and O. brumata (54%; Derks et al., ; International Silkworm Genome Consortium, ). Furthermore, 605 duplicated regions (average length: 1,348 bp, range 809–8,509 bp) were identified in 540 scaffolds.…”
Section: Resultssupporting
confidence: 67%
“…Such resources are urgently needed for various ongoing studies concerning the PPM and implying the development of pan‐genomic markers to disentangle complex demographic scenarios (Leblois et al., ) or to improve the identification (and annotation) of loci subjected to adaptive constraints using genome‐wide scans which detect footprints of selection (M. Gautier, personal communication, July 2017). They will also be essential to characterize the genetic architecture of phenology (see for instance Derks et al., ), of the urticating system (Berardi et al., ) or of traits involved in the adaptation to high temperatures (such as heat‐shock proteins).…”
Section: Introductionmentioning
confidence: 99%
“…As such, the biogeographical history of winter moth might represent an important case study for the role of secondary contact in promoting the genetic diversity of outbreaking pest species. Finally, we hope that this new genetic data, and the discovery of additional biogeographic structuring, can be used in conjunction with the recently published winter moth genome (Derks et al, 2015), to promote the use of winter moth as a model system for future research questions, including studies of local adaptation-a subject for which winter moth has previously been studied in the pregenomics era (Buse & Good, 1996;van Dongen, Backeljau, Matthysen, & Dhondt, 1997;Holliday, 1977; Mohamed Lahbib Ben Jamâa https://orcid. org/0000-0003-1608-2867…”
Section: Con Clus Ionsmentioning
confidence: 98%
“…This species has a broad range of woody host plants including, but not limited to, oak (Quercus), maple (Acer), and birch (Betula) trees in Europe (Wint, 1983), and has long been studied as a model organism for studies of local adaptation (Tikkanen & Lyytikainen-Saarenmaa, 2002;Tikkanen, Woodcock, Watt, & Lock, 2006;Van Dongen, Matthysen, & Dhondt, 1996), and population ecology (Hassell, 1968;Macphee, Newton, & McRae, 1988;Varley & Gradwell, 1960, 1968, and has been at the center of an ongoing debate in regards to whether cyclical outbreaks of geometrid moths (including winter moth) move across western Eurasian from east to west approximately every 10 years (Tenow et al, 2013;but see Jepsen, Vindstad, Barraquand, Ims, &Yoccoz, 2016 andTenow, 2016). In addition, this species has also been the subject of much genetic research, including population structure (Leggett et al, 2011;Van Dongen, Backeljau, Matthysen, & Dhondt, 1998), hybridization (Elkinton, Liebhold, Boettner, & Sremac, 2014;Elkinton et al, 2010;Havill et al, 2017), and a draft genome for this species was recently published (Derks et al, 2015). Yet, the only continent-scale study of winter moth phylogeography (Gwiazdowski, Elkinton, Dewaard, & Sremac, 2013) found little evidence for geographically distinct genetic lineages when the mitochondrial locus cytochrome oxidase I (COI) was analyzed-although it did find support for a division between northern (i.e., Norway, Scotland, and Sweden) and southern European (i.e., all other sampled locations) populations.…”
mentioning
confidence: 99%